Naruto, um aluno com craniofaringioma na educação especial hospitalar : um estudo fenomenológico e existencial inspirado em Paulo Freire - Lima, Hedlamar Fernandes Silva (2018)
This study aims to describe comprehensively "the ways of being with each other in the world" of a six year old patient with craniopharyngioma, who names himself Naruto and who is a pupil from a Special Education School (and non-school) for having become blind due to this complex clinical picture. In order to analyze the ways of being of Naruto, I turn to a phenomenological research method and to the concepts presented in the works of Paulo Freire (1921-1997). In addition to the phenomenological and existential analysis of the student's experiences from the contact with him in the hospital class of the Hospital Nossa Senhora da Glória and in his residence (using for data collection photographs, recordings, informal conversations and videos), a bibliographical review on the topic of "hospital pedagogy" was also made. As well as a brief history of the implantation of this system in Brazil and in the world, a description of its legal bases and an analysis of what it means to educate a child in a hospital, how to organize this space for education and how to promote the patient-student health. For a better understanding about the challenges that the patient-student victim of this disease must face in order to be a human being, a brief exposition on the consequences of craniopharyngioma to the health was also carried out. Concluding, as a result, it turned out that Naruto, regardless of the difficulties of his pathology and his life history, has revealed himself as a presence in the world, with the world and with the others around him.